ANALISIS FAKTOR - FAKTOR YANG MEMPENGARUHI PERMINTAAN TEMPE PADA RUMAH TANGGA DI KELURAHAN TENGGILIS KOTA SURABAYA (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2022)
The purpose of this study is to determine characteristics of people who consume tempe at the Tenggilis Village, to determine factors that affect the demand for soybean in the Tenggilis Village, to measure the amount of public response to the changes in the price of tempe at the Tenggilis. The types and sources of data used in this study are primary data obtained from distributing questionnares to the lokal community, and secondary data obtained from the local government. The conclusion is all the factors affect the demand for soybean in Tenggilis village. The results of calculation of price elasticity show that tempe has an elasticity of 0.786 meaning that tempe is inelastic. The variables of this study include the price of tempe (X1), the number of families (X2), and the level of income (X3) and the level of demand (Y). This research uses descriptive quantitative research. The sample in this study amounted to 97 respondents who were taken through accidental sampling technique. The analytical method used in this research is using multiple linear regression analysis with the help of SPSS 17. We suggest that price of tempe has a very real impact on demand in the Tenggilis village, so that existing tempe producers can increase their tempeh production capacity to meet the tempe needs of the community in Tenggilis village, Surabaya.